PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Kasus Pada Karyawan Divisi Sales PT Surya Agung Indah Megah Cabang Surabaya) - Monikasari, Siti Nur Azizah; Hidayat, Rusdi (Jurnal Bisnis Indonesia, 2019)
This study aims to determine: (1) the effect of job satisfaction and work motivation simultaneously on organizational citizenship behavior on sales employees of PT Surya Agung Indah Megah Branch Surabaya (2) the effect of partial job satisfaction on organizational citizenship behavior on sales employees of PT Surya Agung Indah Magnificent Branch of Surabaya (3) the influence of work motivation partially on organizational citizenship behavior on sales employees of PT Surya Agung Indah Megah Surabaya Branch. This research method uses quantitative methods. The sampling technique uses saturated samples by taking all 38 sales division employees as many as 38 respondents from PT Surya Agung Indah Megah Surabaya Branch. The data analysis technique used is multiple linear regression analysis which is processed using SPSS 25 for windows. Based on the results of this study, Fcount, namely H0 is rejected and H1 is accepted so that it can be concluded that the variable job satisfaction (X1) and work motivation (X2) simultaneously have a significant influence on organizational citizenship behavior (Y) of the Surabaya branch of Surya Agung Indah Megah. The results of the Job Satisfaction calculation, H0 accepted and H1 rejected, this means that job satisfaction (X1) partially has a non-significant effect on organizational citizenship behavior (Y). The results of the Work Motivation count, namely H0 rejected and H1 accepted, this means that work motivation (X2) partially has a significant influence on organizational citizenship behavior (Y) employees of PT Surya Agung Indah Megah Surabaya Branch. Keywords: Job Satisfaction, Work Motivation, Organizational Citizenship Behavior